Good institutions are not enough: Ongoing challenges of East German development - Wendy Carlin (Center for Economic Studies and ifo Institute (CESifo), 2010)
A major theme in accounts of the transitional recession and delayed convergence in post-communist economies is the role of institutions. Yet via unification, East Germany had immediate access to credible, high quality institutions. This paper argues that success in a capitalist economy depends not only on high quality institutions but also on finding one's niche in the international division of labour. East Germany's experience highlights the long shadow cast by the period under communism over the economy's ability to find its comparative advantage in tradeables on a scale adequate for self-sustaining growth.
Keywords: O43; O52; 330; transition; institutions; East Germany; tradeables; convergence; Wirtschaftliche Anpassung; Institutionalismus; Handelbares Gut; Marktnische; Internationale Arbeitsteilung; Neue Bundesländer